Saving Motives and Intention towards Saving of Bulgarian Pomaks - Satsios, Nikolaos; Karamanis, Kostas; Galanou, Aikaterini; Sotiropoulos, Ioannis (International Journal of Economics and Financial Issues, 2020)
This research intends to shed light on the relation between individuals’ saving motives and their intention towards saving, by examining the effect of background characteristics on a sample of 400 Bulgarian Pomaks. Findings revealed that future uncertainties consist the saving motive, which positively relates to the intention towards saving, with university graduates scoring higher on the saving intention scale than other educational groups. The implications of the findings are particularly important for the financial planners and educators since they are the ones who support Bulgarian Pomaks to maintain their standard of living and be prepared for financial uncertainty through saving. Keywords: Saving Motives, Intention towards Saving, Bulgarian Pomak JEL CLassifications: D10, D14. DOI: https://doi.org/10.32479/ijefi.9633